Analisis Kecepatan Dan Arah Aliran Air Tanah Lahan Gambut Desa Dompas Kebupaten Bengkalis (Studi Kasus: Desa Dompas, Kabupaten Bengkalis) - putri, Novalin; Sutikno, Sigit; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Peatland is a type of land that is flammable. One of the causes is land dryness that is caused by the formation of many canal networks. To reduce the possibility of damage to land, a rewetting effort is made. Rewetting is done by building a canal blocker. The construction of canal blocking is an effort to increase the capacity of the water in peatlands, and also to be able to prevent the decrease of water level in peatlands. This study analyzes the velocity and direction of groundwater flow before and after the canal blocking which is measured with the Groundwater Velocimeter instrument on each monitoring well. Based on the groundwater flow analysis which uses the Groundwater Velocimeter method in Dompas Village, Bengkalis Regency, it can be concluded that the highest velocity of the groundwater flow before the canal blocking occured in SP1-2, based on the Image J method which obtained a velocity of 0.09 m/day, and for the visual method, the highest velocity SP 2-4 was 0.28 m/day. While the highest velocity of the groundwater flow after the canal blocking occured in SP 1-4, based on the Image J method which obtained a velocity of 0.107 m/day, and for the visual method, the highest velocity that obtained at SP 2-4 was 0.43 m/day. Keywords: groundwater velocimeter, canal block, peatland